Microstructure and wear behaviour of Ni-based/TiC composite coating - Buytoz, Soner; Kilic, Musa; Carboga, Cemal (Inderscience Enterprises Ltd, 2022)
The purpose of this study was to produce a metal matrix composite by adding TiC into a Ni-based matrix with the tungsten inert gas method and to measure the wear performance. TiC powder was added into the NiCrBSi alloy powders. With increasing current values, decreases in the pore ratio and increases in the density of the eutectic structures and the thickness of the coating layer occurred. In addition, it was determined that increasing energy input improved the mechanical properties. According to XRD results, it was seen that Ni3B, gamma-Ni, CrB, Cr2B, M23C6(Cr23C6), M3C(Fe3C), and TiC complex carbide and boride phases were formed in the coating and the hardness values of these phases increased in the range of 2-2.5 times. Wear tests showed that the hard carbide and borides in the structure caused an overall reduction in the coefficient of friction and weight loss values of the coating layers.
Keywords: cladding; friction of coefficient; microstructure; gamma-Ni; TiC; wear